Sustainable Management of Chlorine Consumption in an Outdoor Swimming Pool: A Case Study of the Silpakorn University Swimming Pool: 10.32526/ennrj/23/20240181 - Santisukkasaem, Umarat (Environment and Natural Resources Journal, 2025)
The general daily maintenance of outdoor swimming pools includes the addition of chlorine for disinfection. Chlorine is a potentially hazardous chemical that is harmful to users, and its excessive addition could lead to health effects in swimmers while insufficient levels may result in inadequate disinfection. This study aimed to optimize chlorine management at the Silpakorn University swimming pool by analyzing the physical and chemical characteristics of outdoor pool water. Initial sampling revealed an unacceptably high residual chlorine concentration of 20 mg/L, exceeding regulatory standards. To address this, a chlorine management strategy was implemented. Chlorine adjustment was conducted by measuring the residual chlorine concentration and calculating the chlorine demand. Post-intervention results indicated that residual chlorine and pH levels were successfully brought within acceptable limits. Further analysis confirmed that parameters such as hardness, ammonia nitrogen, nitrite nitrogen, nitrate nitrogen, suspended and dissolved solids, and total and fecal coliform bacteria met safety standards. Recommendations were given to the pool caretaker, including the use of personal protective equipment (PPE) while handling chlorine, a precise measurement of chlorine (1 kg daily), and regular filtration tank maintenance at least twice a month. Besides improving social and environmental aspects, the optimized chlorine usage resulted in an estimated annual cost saving of 1,213.26 (1 USD ≈ 36.065 THB). This study highlights the importance of sustainable chlorine management in swimming pools, offering a practical approach that can be replicated in similar facilities.